Determinants of The Need for SAK EMKM for EMKM (Empirical Study on EMKM In Jember District) - Oktaviyanti, Faradina Dwi; Moh. Halim; Aspirandi, Rendy Mirwan (West Science Journal Economic and Entrepreneurship, 2024)
Micro, Small and Medium Entities (EMKM) are productive business opportunities owned by individuals or individual business entities that meet the criteria of micro businesses regulated by law. The purpose of this research is to implement and analyze the factors of SAK EMKM needs for EMKM in Jember Regency. The data used in this study are primary data sourced from questionnaires given to EMKM owners in Jember Regency. The results showed that simultaneously the independent variables consisting of owner education, IT understanding, qualitative characteristics of financial statements, SAK EMKM socialization, and business scale had a significant effect on the dependent variable, namely the perceived need for SAK EMKM in Jember Regency. Partially, owner education, IT understanding, qualitative characteristics of financial statements, SAK EMKM socialization, and business scale have a positive effect on the perception of SAK EMKM in Jember Regency.